Literary Neurodiversity Studies - Irish, Bradley J. author. (orcid)0000-0002-8021-6359 Link aut Link
IX, 106 p. 1 illus.
Keywords: This book is a concise but comprehensive introduction to the field of literary neurodiversity studies, a growing approach to literary criticism that has emerged in the past decade. Its three parts are designed to: 1) introduce readers both to the general concept of neurodiversity and to current outlooks, approaches, and key scholarship from literary neurodiversity studies; 2) to present one possible vision of the future of literary neurodiversity studies, by offering an argument about how the field might further entwine with more general research on literary cognition, literary emotion, and literary sensation; and 3) to model for readers how one might perform a neurological reading of a literary text, by offering a sustained analysis of Shakespeare’s Othello. It also contains an extensive bibliography of existing scholarship from literary neurodiversity studies, which will provide an indispensable resource for new and experienced researchers in the field. Bradley J. Irish is an associate professor of English at Arizona State University, Tempe, USA, where he focuses on the literary and cultural history of Renaissance emotion and, more recently, early modern neurodiversity studies. He is the author of Emotion and the Tudor Court: Literature, History, and Early Modern Feeling (2018), Shakespeare and Disgust: The History and Science of Early Modern Revulsion (2023), The Universality of Emotion: Perspectives from the Sciences and Humanities (2024), and The Rivalrous Renaissance: Envy and Jealousy in Early Modern English Literature (2025), and the co-editor of Positive Emotions in Early Modern Literature and Culture (2021), The Routledge Companion to Literature and Emotion (2022), and the forthcoming Neurodiversity in Early Modern English Literature. He is an internationally recognized expert on early modern emotion and is becoming an important contributor to the development of early modern neurodiversity studies.